O reino Visigodo: catolicismo e permanências pagãs - Andrade Filho, Ruy de Oliveira [UNESP] (Universidade Federal de Goias, 2012)
What became accustomed to call “paganism” is undoubtedly one of the most significant forms of what is designated as “popular religiosity”. This expression, which seems useful when a generalization is required, shows all its weakness when a more precise and objective observation of a particular religion is attempted. Would the official visigothic kingdom’s “conversion” to Catholicism, with Recardo (586-601) at the Council of Toledo of 589 have effectively matched to the “conversion” of this kingdom’s population? Firstly, it is necessary to consider, in beyond the exalting intentions of the sources of that moment, that mass conversions do not imply a radical change in the convictions and religious practices of an entire people. Secondly, that “conversion” and “Christianization” are not synonymous. “Religiosity”, which includes the “conversion”, implies a fundamental religious attitude, which can simply be interior and personal. On the other hand, “religion”, in which “Christianization” is included, would correspond to a public aspect, institutionalized, which elaborates a set of techniques aiming, as in the case of “religiosity”, the guarantee of the supernatural Thus, elevated to the position of “official religion,” Catholic Christianity would live with a series of rites, rituals, devotions, from the previous “religiosity” that, through its ecclesiastical perspective, would be reprehensible, considered marginal and something that would lead to error. However, on the eve of the Muslim invasion in 711, not only among the laity but even in ecclesiastical segments, the manifestations of the “paganism” still were aim of coactive condemnation in the Catholic kingdom of Toledo’s councils.

O que se costumou chamar de “paganismo” é, sem dúvida, uma das formas mais significativas daquilo que se costumou designar por “religiosidade popular”. Tal expressão, que parece útil quando se pretende uma generalização, mostra toda sua fragilidade quando se tenta uma observação mais precisa e objetiva de uma determinada religiosidade. A “conversão” oficial do reino visigodo ao catolicismo, com Recardo (586-601) no concílio de Toledo de 589 teria, efetivamente, correspondido à “conversão” da população desse reino? Em primeiro lugar, é necessário que consideremos, para além das intenções exaltadoras das fontes desse momento, que as “conversões” em massa não implicam uma mudança radical nas convicções e práticas religiosas de todo um povo. Em segundo, que “conversão” e “cristianização” não são sinônimos. A “religiosidade”, onde se insere a “conversão”, implica uma atitude religiosa fundamental, que pode ser simplesmente interior e pessoal. Por seu turno, a “religião”, que engloba a “cristianização”, corresponderia a um aspecto público, institucionalizado, que elabora um conjunto de técnicas dirigidas que visa, como no caso da “religiosidade”, a garantia do sobrenatural. Assim, alçada ao posto de “religião oficial”, o cristianismo católico passaria a conviver com uma série de ritos, cultos, devoções, oriundos da “religiosidade” anterior e que, sob sua ótica eclesiástica, seriam condenáveis, consideradas marginais e que conduziriam ao erro. Contudo, às vésperas da invasão muçulmana em 711, não somente entre os laicos mas inclusive nos segmentos eclesiásticos, as manifestações do chamado “paganismo” ainda eram alvo de condenações coercitivas nos concílios católicos do reino de Toledo.
The visigothic kingdom: catholicism and pagan permanencies
Keywords: Christianization; Conversion; Paganism; Antiguidade Tardia; Cristianismo; Igreja; Monarquia; Paganismo; Visigodos